The Effect Vision Exercises on the improvement of Visual Attention Concentration and Serving Performance Accuracy in Tennis - Hafez, Abd alhalim (Journal of Physical Education, 2016)
The problem of the research lies in not including visual exercises in teaching programs. The researcher aimed at preparing visual exercises and identifying their effect on improving attention concentration and serving accuracy in tennis. The subjects were (40) female students from the college of physical education and sport sciences/ university of Baghdad. The subjects were divided according to their sections into controlling group and experimental group. The experimental program included pretests, followed by the teaching exercises and ended with posttests. The teaching program consisted of two teaching sessions per week for two months making a total of (16) teaching unit. The data was collected and treated using proper statistical methods. The researcher concluded that visual exercises contribute to the learning and development of visual concentration and serving accuracy.